2007
DOI: 10.1021/la700893w
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Structure of Water on SiO2 Films on Si Investigated by Kelvin Probe Microscopy and in Situ X-ray Spectroscopies

Abstract: The growth of water on thin SiO 2 films on Si wafers at vapor pressures between 1.5 and 4 torr and temperatures between -10 and 21 o C has been studied in situ using Kelvin Probe Microscopy and X-ray photoemission and absorption spectroscopies. From 0 to 75% relative humidity (RH) water adsorbs forming a uniform film 4-5 layers thick. The surface potential increases in that RH range by about 400 mV and remains constant upon further increase of the RH. Above 75% RH the water film grows rapidly, reaching 6-7 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
220
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(253 citation statements)
references
References 33 publications
22
220
1
2
Order By: Relevance
“…Contact potential difference measurements combined with XPS analysis under ambient pressure have shown that water molecules can be adsorbed on oxidized silicon with a significant increase of the contact potential (net positive charge or dipole on the surface) of about 400 meV, which essentially occurs between 2 and 5 water monolayers. 51 This result shows that H 2 O vapor adsorption can significantly decrease the barrier height in oxidized patches.…”
Section: Charge Transfer Effect On Interface Barrier Heightsmentioning
confidence: 83%
See 1 more Smart Citation
“…Contact potential difference measurements combined with XPS analysis under ambient pressure have shown that water molecules can be adsorbed on oxidized silicon with a significant increase of the contact potential (net positive charge or dipole on the surface) of about 400 meV, which essentially occurs between 2 and 5 water monolayers. 51 This result shows that H 2 O vapor adsorption can significantly decrease the barrier height in oxidized patches.…”
Section: Charge Transfer Effect On Interface Barrier Heightsmentioning
confidence: 83%
“…In addition, hydrophilic silicon oxide regions may also favor the physisorption of polar water molecules and contribute to modify the interface potential. 51 In order to get some insight in the dynamics of the molecular monolayer/SiO 2 /Si system, this work investigates the dipolar relaxation signature of chemisorbed and physisorbed polar moieties over a broad electrical bias and temperature range.…”
mentioning
confidence: 99%
“…It can be seen that there are two transitions in the adhesion force as shown in Eq. (11). The first transition is from solid-solid to solid-solid ?…”
Section: Resultsmentioning
confidence: 99%
“…After 10 % RH the monolayer starts to grow in multilayers and at about 30 % RH 3 monolayers are formed. The water will be considered as bulk only if the number of monolayers is greater than 3 [10,11]. So, water will be in an ordered form from 10 to 30 % RH.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation